TOWARDS A RECOGNISED RIGHT TO A SHARED CULTURE AT THE REGIONAL LEVEL: How Will ASEAN Address Diversity? - Arsika, I Made Budi; Suyatna, I Nyoman; Purwani, Sagung Putri M.E (Jurisdictie: Jurnal Hukum dan Syariah, 2024)
ASEAN documents have officially upheld the principle of unity in diversity and agreed on the spirit of one identity and community. However, there is a pronounced tendency for ASEAN countries to struggle with each other with several differences, including cultural tensions. This paper aims to analyse the possibility of recognising a regionally shared culture as jointly claimed collective cultural rights by taking the example of Intangible Cultural Heritage ICH. It is designed as legal research applying statutory, historical, conceptual, and comparative approaches. This research collects norms and principles covering the issues of ICH and cultural rights and conducts a literature study, suggesting that cultural rights, which represent the intersecting of cultural and human rights aspects, have yet to be fully understood as collective cultural rights. ICH is an example of how ASEAN countries are sometimes heated up in non-harmony relations. The possibility of recognising a regionally shared culture in the context of collective cultural rights then, more or less, relies on the ongoing development of the Narrative of ASEAN Identity, the routine convening of human rights dialogues, and the initiation of the ASEAN Cultural Heritage List. These findings are then expected to be considered by ASEAN policymakers. Dokumen-dokumen ASEAN mencatumkan iktikad untuk menjunjung tinggi prinsip persatuan dalam keberagaman dan menyepakati semangat satu identitas dan komunitas. Dalam kenyatannya, negara-negara anggota ASEAN justru bergelut dengan sejumlah persoalan antara negara yang satu dengan negara lainnya, termasuk mengenai ketegangan budaya. Artikel ini bertujuan untuk menganalisis kemungkinan mengakui budaya bersama secara regional sebagai hak budaya kolektif yang diklaim bersama dengan mengambil contoh warisan budaya tak benda (WBTB). Artikel ini dirancang sebagai penelitian hukum yang menggunakan pendekatan perundang-undangan, sejarah, konsep, dan perbandingan. Penelitian dilakukan dengan mengumpulkan norma-norma dan prinsip-prinsip yang mengatur isu WBTB dan hak budaya serta melakukan studi literatur. Artikel ini menyimpulkan bahwa hak budaya, yang mewakili persilangan antara aspek budaya dan hak asasi manusia (HAM), belum sepenuhnya dipahami sebagai hak budaya kolektif. WBTB menjadi contoh bagaimana negara-negara ASEAN terkadang berada dalam hubungan yang tidak harmonis antara satu dengan lainnya. Adapun kemungkinan untuk mengakui budaya bersama secara regional dalam konteks hak budaya kolektif dapat disandarkan pada pengembangan Narasi Identitas ASEAN, penyelenggaraan dialog HAM secara rutin, dan upaya pembentukan Daftar Warisan Budaya ASEAN. Temuan-temuan ini diharapkan dapat dipertimbangkan oleh para pengambil kebijakan di ASEAN.